Is external control important for internal control? - Busseniers, Evo (Journal of Sociocybernetics, 2016)
In cybernetics, the basic assumption is that systems aim for control. But what and how are they controlling? I dierentiate two categories of control: internal and external control. In external control, one starts from outside, and tries to determine the environment completely. While with internal control, one’s own aspirations are taken as a starting point, and useful synergies with the environment are sought. I’ll dene these con- cepts in cybernetic terms, and argue why they are not necessary related. There are two aspects in this dierence. The rst lies in the locality: is there an aim for global control, or only for control in the immediate envi- ronment? There is also a dierence in what one tries to change. An agent could adapt its links, or try to change either the methods or the goals of its neighbors. Several of these cases will be further explored by giving an existing model that falls under this circumstances. All of these models will be put into an overarching framework. The model of controllability is a model about global control, while the others model local control, based on neural net- works or perceptual control theory.